Targeted degradation of bromodomain-containing protein 4 enabled by reactive oxygen species-activatable NanoPROTACs as an efficient strategy to reverse liver fibrosis in chronic liver injury - Bi, Tao; Liang, Pan; Zhao, Qixin; Wu, Jiao; Zhou, Yanan; Xu, Yunke; Fan, Xuehui; Yang, Guoqiang; Sun, Qin; Ren, Wei; Yang, Yingcheng; Liu, Zengjin (Journal of medicinal chemistry, 2025)
Liver fibrosis is an inadequate response to tissue stress, with reactive oxygen species (ROS) overproduction in activated hepatic stellate cells (aHSCs). Bromodomain-containing protein 4 (BRD4) was found to be upregulated in aHSCs and has been identified as an effective target for the treatment of liver fibrosis. However, inhibition of BRD4 with traditional kinase inhibitors achieved only limited success because of its low therapeutic efficiency. Furthermore, the exact mechanism by which BRD4 regulates liver fibrosis remains unclear and needs to be elucidated. In this work, we proposed an efficiency strategy, i.e., targeted degradation of BRD4 by ROS-activatable NanoPROTACs, for the treatment of liver fibrosis, both in vitro and in vivo. More importantly, we clarified the mechanism by which BRD4 regulates liver fibrosis. Thus, this strategy may represent an alternative to previously reported strategies and may be extensively applied to the design of ROS-activatable proteolysis-targeting chimeras for the treatment of other organ fibrosis.
Online verfügbar: 06. März 2025
Gesehen am 18.08.2025